Estudo toponímico em Libras dos municípios da Bahia: memória, identidade e resistência cultural - Ferreira, Daniela Betânia dos Santos (2025)
In recent years, studies focused on toponymy have gained significant prominence, sparking the interest of researchers in various regions of Brazil. This movement has enabled a broader understanding of the social, cultural, historical, and linguistic dimensions that permeate the oral languages used in the country. In the field of Brazilian Sign Language (Libras), investigations into toponymy have developed gradually, establishing themselves as an emerging research area and revealing the need to expand linguistic approaches applied to sign languages. Within this context, this thesis aims to analyze the toponymic signs referring to municipalities in Bahia in Libras, with an emphasis on understanding the motivational processes that guide their formation. The study is based on the premise that the creation and dissemination of toponymic signs uniquely express identity and cultural aspects of deaf communities, while also reflecting the interaction between geographic space, language, and visual experience. To achieve this objective, a survey was conducted of the 417 municipalities in the state of Bahia, with the purpose of identifying those that have signs in use in the deaf community. As a result of this mapping, toponymic signs were identified in 149 municipalities, which comprise the corpus analyzed in this research. This study adopts a qualitative and descriptive approach, based on linguistics and lexicology, supported by an interdisciplinary theoretical and methodological framework that articulates linguistic studies of Libras (Felipe, 1989; 2006; Quadros, 2019; 2025; Quadros and Karnopp, 2004; Strobel, 2008; 2009; Ferreira-Brito, 1995), lexicological research (Biderman, 1998; 2001), general toponymic investigations (Dick, 1990; 1992; 1999; Carvalho, 2014; Francisquini, 1998; Lima, 1997; Seabra, 2004; Isquerdo, 1996) and toponymic studies in Libras (Barreiros and Ferreira, 2018; (Ferreira, 2019; Jesus, 2019; Sousa, 2018; 2019; 2023; Souza Júnior, 2012; Sousa et al., 2025), among others. The results demonstrate the diversity of motivational strategies employed in the creation of toponymic signs, ranging from the iconicity of visual elements characteristic of the place to historical, cultural, and identity references. The analysis also highlights the existence of regions with denominative gaps, which reinforces the importance of linguistic policies aimed at expanding and systematizing the lexicon in Libras (Brazilian Sign Language). The contribution of this thesis is thus expressed in multiple dimensions: in the theoretical field, by consolidating toponymy in Libras as an autonomous area of study; in the methodological field, by proposing data collection and classification instruments adapted to visual-spatial languages; and in the applied field, by offering digital products that broaden access to and dissemination of linguistic knowledge. As a final product, the Libras Bahia website and the homonymous YouTube channel were developed, bringing together videos, descriptive sheets, and classifications of the signs studied. These bilingual, dynamic, and accessible repositories are intended to directly benefit the deaf community, teachers, interpreters, and researchers, promoting the appreciation of Libras (Brazilian Sign Language) and the dissemination of the cultural and linguistic diversity thatcharacterizes Bahia.